The Effectiveness of a Program Based on the Schwartz Model for Developing Mathematical Communication Skills For Eighth Grade Students. - غصون, سماح (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The research aims to study the effectiveness of a program based on the Schwarts model in developing mathematical communication skills among a sample of (60) students, and the members of the two groups were randomly chosen from the classes of basic education Schools in Lattakia. The researcher applied to the experimental group a program based on the Schwartz Model while applying to the control group the usual way, and started testing mathematical communication skills and then collected data and analyzed it and reached the following results: There is a statistically significant difference at the level of 0.5% between the average scores of the experimental group, studentsin the mathematical communication skills test. The effectiveness of the Schwartz Model in teaching basic eighth graders in mathematics. The research ended with a set of conclusions and recommendations such as interest in mathematical communication skills in learning mathematics.